Service use and costs in adolescents with pain and suicidality: a cross-sectional study - Hinze, V; Ford, T; Gjelsvik, B; Byford, S; Cipriani, A; Montero-Marin, J; Ganguli, P (Elsevier, 2022)
Background: Persistent/recurrent pain for more than three months and suicidality (suicide and self-harm related thoughts and behaviours) are serious and co-occurring health problems in adolescence, underscoring the need for targeted support. However, little is known about service use and costs in adolescents with pain-suicidality comorbidity, compared to those with either problem alone. This study aimed to shed light on service use and costs in adolescents with pain and/or suicidality, and the role of individual and school characteristics. Methods: We analysed cross-sectional, pre-intervention data from a large cluster randomised controlled trial, collected between 2017 and 2019 on a representative sample of 8072 adolescents (55% female; aged 11–15 years; 76% white) in 84 schools in the UK. We explored service use settings, covering health, social, educational settings, and medication for mental health problems over three months. Data were analysed using descriptive statistics and two-part hurdle models to obtain odds ratios (ORs) and incident rate ratios (IRRs). Findings: 9% of adolescents reported comorbidity between pain and suicidality, 11% only suicidality, 13% only pain, and 66% neither pain nor suicidality. Approximately 55% of adolescents used services, especially general practitioner visits, outpatient appointments for injuries and contacts with a school nurse or pharmacist. Compared to adolescents with neither pain nor suicidality: (i) adolescents with pain (OR 3.79, 95% CI 2.63–5.48), suicidality (1.68, 1.12–2.51), and pain-suicidality comorbidity (2.35, 1.26–4.41) were more likely to use services and (ii) if services were used, they were more likely to have higher total costs (Pain: IRR 1.25, 95% CI 1.11–1.42; Suicidality: 1.27, 1.11–1.46; Comorbidity: 1.57, 1.34–1.85). Interpretation: In our study, adolescents with pain and suicidality reported increased contact with health, social, and educational services, which could provide an opportunity for suicide prevention. Given the diversity of identified settings, multi-sector suicide prevention strategies are paramount.